Building Rural Poultry Supply-Chains To Enhance Incomes through Community-Driven Interventions : Case Study from Jharkhand, India - Newton-Lewis, Tom; Jha, Avadesh; Singh, Pratyush Ranjan; Nagpal, Phalasha; Bihari, Bipin (World Bank, Washington, DC, 2020)
Layer farming is an income-generating livelihood activity wherein egg-laying poultry birds are raised by a household for the purpose of egg production on a commercial scale. The few traditional rural producer households that are engaged in layer farming in Jharkhand are constrained by high input costs (such as pullets, feed, vaccinations), a high disease-based mortality rate, and poor access to credit, making it a less remunerative income source. Cereal-based feed is imported from Andhra Pradesh, Bihar and Madhya Pradesh, thereby escalating input costs1. Jharkhand is dependent on egg imports from neighboring states, thus presenting a promising marketing opportunity within the state. However, low and fragmented production, coupled with poor market linkages and inefficiencies make it a challenge for households to realize remunerative prices from their produce. As a part of its diversified and resilient production systems component, the JOHAR project has invested in layer farming under the livestock development sub-component, with the objective of improving rural livelihoods in Jharkhand. This note investigates a layer co-operative's federation, operational and production model as well as financial feasibility. An operational co-operative in Basia block, of Gumla district, was used as a case and analyzed in detail.